Groundwater quality assessment and hydrochemical characteristics in Wera Didjo, Southern Ethiopia - Fantu Zeleke; Abel Abebe; Jagadeshan Gunalan (Journal of Degraded and Mining Lands Management, 2022)
Groundwater quality assessment study was conducted in Wera Dijo, Southern Ethiopia. The study's objective is to understand water chemistry suitability for domestic and irrigation activities. In the study area, only regional hydrochemistry work has been done; hence this study focused on the detailed water chemistry of the study area. Twenty-eight shallow and deep water samples were collected, and major physical and chemical parameters were studied. The important hydrochemical facies of water present throughout this region are Ca–Mg–HCO3, Ca–Mg–SO4 and Na–HCO3–Cl. Except for fluoride, sodium, and potassium ion, the levels of major cation and anion were found to be below the World Health Organization's allowable limits for drinking purposes in the majority of the study area. The fluoride ion in groundwater exceeded the highest allowable amount of 1.5 mg/L for drinking water in fifteen of the samples. The sodium percentage, permeability index, sodium absorption ratio and The United States Salinity Laboratory (USSL) categorization were used to evaluate the water in this study location for irrigation purposes. Based on several water quality parameters overall, the research area water chemistry was suitable for drinking, agricultural activity and industrial use.